Insubordination - Evans, Nicholas; 渡辺, 己 (Typological Studies in Language, 2016)
The phenomenon of insubordination can be defined diachronically as the recruitment of main clause structures from subordinate structures, or synchronically as the independent use of constructions exhibiting characteristics of subordinate clauses. Long marginalised as uncomfortable exceptions, insubordinated clause phenomena turn out to be surprisingly widespread, and provide a vital empirical testing ground for various central theoretical issues in current linguistics - the interplay of langue and parole, the emergence of structure, the question of where productive syntactic rules give way to constructions, the role of prosody in language change, and the question of how far grammars are produced by isolated speakers as opposed to being collaboratively constructed in dialogue. This volume - the first book-length treatment on the topic - assembles studies of languages on all continents, by scholars who bring a range of approaches to bear on the topic, from historical linguistics to corpus studies to typology to conversational analysis.